Research Update: Development of Plant-based Diets for Florida pompano Trachinotus carolinus - Novriadi, Romi; Davis, D. Allen (Indonesian Aquaculture Society (MAI), 2018)
The development of sustainable and economically sound practical diet in the coming years will depend on the reduction of fish meal and the increased inclusion of sustainable protein sources. Over the years, our laboratory has systematically reduced the inclusion levels of fish meal and other animal protein sources by using a range of alternative plant-protein sources. These diets may be further improved through the use of specialized proteins, supplements for limiting amino acids, enzyme and attractants. Good success has been seen with corn protein concentrates, advanced processing products of soybean meal, such as soy protein concentrates and advanced soy product (enzyme treated or fermented soy). Based on the results of our research, the proportion of animal meal can be reduced to 12 % in our current formulations without any detrimental effects on pompano performance and nutrient retention. In addition, the use of fermented soy or the combination of enzyme-treated soy with proper inclusion level of squid hydrolysates as an attractant has proven to improve the functional properties of SBM and lead to better liver and intestine condition of pompano. Considering the sizeable body of knowledge concerning nutrition for Florida pompano, all information taken from this species could be used as the starting point to develop better feed formulations for Silver pompano production in Indonesia.